Ionic Liquid-assisted Synthesis of Cellulose/TiO2 Composite and Photocatalytic Performance - ZHU Mo-shuqi; LIN Chun-xiang; LUO Wei; LIU Yi-fan; LIU Ming-hua (Cailiao gongcheng, 2016)
Cellulose/TiO2 composite was prepared by sol-gel method using the ionic liquid BMIMCl as reactive medium and Ti(OBu)4 as a precursor. The synthesis conditions were optimized by single-factor experiment. The structure and properties of the composite were characterized by scanning electron microscope (SEM),X-ray diffraction(XRD),Fourier transform infrared spectoscopy(FT-IR),UV-vis-diffuse reflectance spectroscope(DRS) and thermogravimetric (TG) analysis. The photocatalytic activity of the composite was investigated via testing the photodegradation of methyl orange in aqueous suspension under UV-light. The results show that the high active photocatalytic composite is prepared by using ionic liquid BMIMCl as medium at room temperature and atmospheric pressure. The photo catalytic degradation rate of composite on methyl orange(MO) reaches 97.09% in 80min. Comparing with bare TiO2, the degradation rate of MO increases by 37%. Moreover, the composite still shows 62.66% degradation rate towards MO after recycling 4 times.